The Relationship between Sperm Morphometry and Sperm Competition in Local Goats of Central Java, Indonesia - S B Wibowo; E T Setiatin; E Kurnianto (Media Peternakan, 2013)
The objective of this study was to examine the relationship between sperm morphometry and sperm competition in local goats. Forty bucks were used in this study, consisted of 4 breeds namely Ettawa Grade Goat (EGG), Kejobong Goat (KJG), Kacang Goat (KCG), and Jawarandu Goat (JWG), each breeds consisted of 10 bucks. GLM, REG and DISRCRIM procedures of SAS were used to compute all data observed. UPGMA of MEGA 5 was used to illustrate the genetic distance among breeds. The result showed that there were differences in the sperm morphometry among 4 breeds of goats (P<0.05). Sperm length positively related to the level of sperm competition in all local goats (P<0.05) although the value of coefficient of determinant was low (r2= 0.0043). Within breed analysis showed that there was no positive relationship between sperm length and level of sperm competition in EGG and JWG goats. Midpiece area positively related to the principal piece (P<0.05). Sperm morphometry had a significant positive relation to sperm competition in local goats of Central Java.